Human CLASP1 is an outer kinetochore component that regulates spindle microtubule dynamics - Maiato, H (2003)
One of the most intriguing aspects of mitosis is the ability of kinetochores to hold onto the plus-ends of dynamic microtubules that are actively gaining or losing tubulin subunits. Here we show that the microtubule-associated protein CLASP1 is localized preferentially near the plus-ends of growing microtubules during spindle formation and is also a component of a novel region that we term the outer kinetochore corona. A truncated form of CLASP1 lacking the kinetochore-binding domain behaves as a dominant-negative, leading to the formation of unique single or double asters comprised of radial arrays of microtubule bundles that are highly resistant to depolymerization. Microinjection of cells with antibodies specific to CLASP1 causes bipolar spindles to collapse, forming bipolar or monopolar arrays of microtubules with chromosomes buried in the interior. Suppression of microtubule dynamics in injected cells rescues the kinetochore association with plus ends of microtubules at the periphery of the asters. Our data suggest that CLASP1 is required for kinetochore-associated microtubules to exhibit normal dynamic behaviour.